الدور التنموي للمؤسسات الصغيرة والمتوسطة - دراسة مقارنة بين حالة الجزائر و تونس - شروق كافي; سلمى عيون (My University, 2022)
The aim of the research in general is to identify the development role of SMEs in Tunisia and Algeria and the most important support and rehabilitation programs for these institutions and the problems hindering them in the performance of their roles, and was used to study the subject analytical descriptive approach, the most important results of the study were the marginal role played by SMEs in achieving and promoting economic development in Algeria and Tunisia due to the entanglement of a range of administrative, technical, financial, organizational and marketing problems. ............................................................... يهدف البحث بشكل عام إلى التعرف على الدور التنموي للمؤسسات الصغيرة والمتوسطة في تونس والجزائر وأهم برامج الدعم والتأهيل لهذه المؤسسات والمشكلات التي تعوقها في أداء أدوارها، وتم الاستعانة بدراسة الموضوع التحليلي وفي المنهج الوصفي، كانت أهم نتائج الدراسة هو الدور الهامشي الذي تلعبه المؤسسات الصغيرة والمتوسطة في تحقيق وتعزيز التنمية الاقتصادية في الجزائر وتونس بسبب تشابك مجموعة من المشكلات الإدارية والفنية والمالية والتنظيمية والتسويقية.